A Pathologist’s Dilemma: Mesenteric Cystic Lymphangioma versus Mesenteric Cyst - Ketaki Makarand Deshpande; Vijayalaxmi M. Dhorigol; Vijay C Pujar (Journal of the Scientific Society)
Mesenteric cystic lymphangioma is a rare malformation of the lymphatic system. The incidence is very low (1 per 250,000). Although these entities usually follow a benign course, varying patterns of clinical presentations and overlapping features with chylolymphatic cysts, the histopathological diagnosis becomes tricky. Here, we report the case of intra-abdominal mesenteric cystic mass. A 10-year-old male patient presented with abdominal swelling and discomfort; provisional clinical diagnosis of chylolymphatic cyst was made; surgical excision of the cystic mass along with the bowel loop was done. Grossly, the cyst was congested externally with multiloculations inside and drained with whitish fluid. The multiple dilated lymphatic channels were surrounded by loose fibrocollagenous connective tissue on microscopic examination. It is important to differentiate mesenteric cystic lymphangioma from chylolymphatic cyst, since lymphangioma, although rare, can follow the invasive course. Histopathological examination is the gold standard for differentiating mesenteric cysts and diagnosing mesenteric cystic lymphangioma, and studying the literature was an out of common experience.